The influence of cell wall bound calcium, cell number and size on the development of mealiness in 'Forelle' pear. Evaluation of X-ray CT and NIR as non-destructive techniques for mealiness detection - Muziri, Tavagwisa (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.